Systemic immunoglobulin light chain amyloidosis - Merlini, Giampaolo; Dispenzieri, Angela; Sanchorawala, Vaishali; Schönland, Stefan; Palladini, Giovanni; Hawkins, Philip N.; Gertz, Morie A. (Nature reviews. Disease Primers, 2018)
Systemic immunoglobulin light chain amyloidosis is a protein misfolding disease caused by the conversion of immunoglobulin light chains from their soluble functional states into highly organized amyloid fibrillar aggregates that lead to organ dysfunction. The disease is progressive and, accordingly, early diagnosis is vital to prevent irreversible organ damage, of which cardiac damage and renal damage predominate. The development of novel sensitive biomarkers and imaging technologies for the detection and quantification of organ involvement and damage is facilitating earlier diagnosis and improved evaluation of the efficacy of new and existing therapies. Treatment is guided by risk assessment, which is based on levels of cardiac biomarkers; close monitoring of clonal and organ responses guides duration of therapy and changes in regimen. Several new classes of drugs, such as proteasome inhibitors and immunomodulatory drugs, along with high-dose chemotherapy and autologous haematopoietic stem cell transplantation, have led to rapid and deep suppression of amyloid light chain production in the majority of patients. However, effective therapies for patients with advanced cardiac involvement are an unmet need. Passive immunotherapies targeting clonal plasma cells and directly accelerating removal of amyloid deposits promise to further improve the overall outlook of this increasingly treatable disease.
Gesehen am 06.04.2020